Understanding low inflation in the euro area from 2013 to 2019: Cyclical and structural drivers - Gerrit Koester; Eliza Magdalena Lis; Christiane Nickel; Chiara Osbat; Frank Smets (European Central Bank (ECB), 2021)
From 2013 up to the launch of the ECB's strategy review in January 2020, inflation in the euro area was low and over-predicted. This low inflation during the years 2013-19 can be attributed to a combination of interconnected factors. Cyclical developments account for a substantial share of the fall in underlying inflation, mainly in the first part of the low inflation period. Additionally, there is evidence that an underestimation of the amount of economic slack and less well-anchored longer-term inflation expectations, in combination with monetary policy in the euro area being constrained by the effective lower bound, have played an important role in the long period of subdued inflation. Ongoing disinflationary structural trends (such as globalisation, digitalisation and demographic factors) are likely to have had a dampening effect on inflation over the last few decades, but were in themselves not the main drivers of low inflation in the euro area from 2013 to 2019. However, as they could not have been easily offset by interest rate policy in an effective lower bound environment, they might also have contributed to the more subdued inflation dynamics in the euro area from 2013 to 2019.
Keywords: C51; E31; E32; E37; E52; F62; J11; J30; 330; Monetary policy review; HICP inflation; underlying inflation; low inflation; effective lower bound